Exploring and expanding capabilities, sustainability and gender justice in science teacher education : case studies in Zimbabwe and South Africa - Chikunda, Charles (Rhodes University, Faculty of Education, Department of Education, 2013)
The focus of this study was to explore and expand capabilities, sustainability and gender justice in Science, Mathematics and Technical subjects (SMTs) in teacher education curriculum practices as a process of Education for Sustainable Development in two case studies in Zimbabwe and South Africa. The study begins by discussing gender and science education discourse, locating it within Education for Sustainable Development discourse. Through this nexus, the study was able to explore gender and sustainability responsiveness of the curriculum practices of teacher educators in Science, Mathematics and Technical subjects; scrutinise underlying mechanisms that affect (promote or constrain) gender and sustainability responsive curriculum practices; and understand if and how teacher education curriculum practices consider the functionings and capabilities of females in relation to increased socio-ecological risk in a Southern African context. Influenced by a curriculum transformation commitment, an expansive learning phase was conducted to promote gender and sustainability responsive pedagogies in teacher education curriculum practices. As shown in the study, the expansive learning processes resulted in (re)conceptualising the curriculum practices (object), analysis of contradictions and developing new ways of doing work. Drawing from the sensitising concepts of dialectics, reflexivity and agency, the study worked with the three theoretical approaches of Cultural Historical Activity Theory (CHAT), feminist theory and capabilities theory. The capability and feminist lenses were used in the exploration of gender and sustainability responsiveness in science teacher education curriculum practices. CHAT, through its associated methodology of Developmental Work Research, offered the opportunity for researcher and participants in this study to come together to question and analyse curriculum practices and model new ways of doing work. Case study research was used in two case studies of teacher education curriculum practices in Science, Mathematics and Technical subjects, one in Zimbabwe and one in South Africa. Each case study is constituted with a networked activity system. The study used in-depth and focus group interviews and document analysis to explore gender and sustainability responsiveness in curriculum practices and to generate mirror data. Inductive and abductive modes of inference, and Critical Discourse Analysis were used to analyse data. This data was then used in Change Laboratory Workshops, where double stimulation and focus group discussions contributed to the expansive learning process. Findings from the exploration phase of the study revealed that most teacher educators in the two case studies had some basic levels of gender sensitivity, meaning that they had ability to perceive existing gender inequalities as it applies only to gender disaggregated data especially when it comes to enrolment and retention. However, there was no institutionalised pedagogic device in place in both case studies aimed at equipping future teachers with knowledge, skills, attitudes and values to promote aspects of capabilities (well-being achievement, wellbeing freedom, agency achievement and agency freedom) for girls in Science, Mathematics and Technical subjects. Science, Mathematics and Technical subjects teacher educators' curriculum practices were gender neutral, but in a gendered environment. This was a pedagogical tension that was visible in both case studies. On the other hand, socio-ecological issues, in cases where they were incorporated into the curriculum, were incorporated in a gender blind or gender neutral manner. Social ecological concerns such as climate change were treated as if they were not gendered both in their impact and in their mitigation and adaptation. It emerged that causal mechanisms shaping this situation were of a socio-political nature: there exist cultural differences between students and teacher educators; patriarchal ideology and hegemony; as well as other interfering binaries such as race and class. Other curriculum related constraints, though embedded in the socio-cultural-political nexus, include: rigid and content heavy curriculum, coupled with students who come into the system with inadequate content knowledge; and philosophy informing pedagogy namely scientism, with associated instrumentalist and functionalist tenets. All these led to contradictions between pedagogical practices with those expected by the Education for Sustainable Development framework. The study contributes in-depth insight into science teacher education curriculum development. By locating the study at the nexus of gender and Science, Mathematics and Technical subjects within the Education for Sustainable Development discourse, using the ontological lenses of feminist and capabilities, it was possible to interrogate aspects of quality and relevance of the science teacher education curriculum. The study also provides insight into participatory research and learning processes especially within the context of policy and curriculum development. It provides empirical evidence of mobilising reflexivity amongst both policy makers and policy implementers towards building human agency in policy translation for a curriculum transformation that is critical for responding to contemporary socio-ecological risks.,Microsoftï¿½ Word 2010,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Science teachers -- Training of -- South Africa -- Case studies; Science teachers -- Training of -- Zimbabwe -- Case studies; Mathematics teachers -- Training of -- South Africa -- Case studies; Women in education -- South Africa -- Case studies; Women in education -- Zimbabwe -- Case studies; Environmental education -- Study and teaching -- Case studies; Curriculum planning -- South Africa; Curriculum planning -- Zimbabwe